PENDIDIKAN BERBASIS DAKWAH SEBAGAI UPAYA DALAM MEMBANGUN KARAKTER DAN KESADARAN BERAGAMA DI ERA POST TRUTH - Taufiq, Taufiq; Lasido, Nur Allan; Arief, Muyassir (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
The post-truth era has presented serious challenges in social, political, and religious life, where objective facts are often trumped by emotions and personal beliefs. This phenomenon has resulted in a character crisis and a weakening of religious awareness, especially among the younger generation living in a digital information flow without value filters. This paper aims to conceptually examine da'wah-based education as a strategy for building character and religious awareness amidst the challenges of the post-truth era. The method used is descriptive qualitative research with a literature study approach. The results of the study indicate that da'wah-based education that integrates the values of tabligh, ta'lim, tarbiyah, and tazkiyah is able to foster students holistically, both intellectually, emotionally, and spiritually. Da'wah in education not only conveys teachings normatively, but also touches on the dimensions of awareness, habituation, and contextualization of religious values in real life. In its implementation, a collaborative strategy is needed between teachers, families, educational institutions, and the intelligent and ethical use of digital media. Thus, da'wah-based education has strong relevance in forming a generation that is morally resilient, critical in thinking, and religiously conscious amidst the post-truth reality.